Pentti Linkola's Ecofascism and the Environmental Crisis: A Re-evaluation of the Concept of Humanity - Rama Dony, Ahmad; Dwiputri Maharani, Septiana (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2025)
The global environmental crisis has posed an urgent challenge for humanity to reconsider its relationship with nature. The idea of ecofascism proposed by Pentti Linkola has attracted attention because it offers a controversial solution to environmental problems. This research explores and re-evaluates the concept of humanity within the framework of ecofascism proposed by Pentti Linkola, using a human philosophy review approach. This research uses a qualitative method with the analytical framework of description, interpretation, and critical analysis of Linkola's humanitarian views. This research identifies the perspective of human philosophy in ecofascism. In addition, this research also explores the implications of reassessing the concept of humanity on human mindset and actions in overcoming the global environmental crisis. By integrating human philosophy perspectives, this research aims to provide a deeper understanding of the complex relationship between ecofascism, the concept of humanity, and the environmental challenges facing humanity. This study's results show that one way to overcome the environmental crisis offered by Linkola is implementing a fascist government with ecological considerations. Linkola offers to regulate the human population, ban foreign languages, control obesity and height, and limit the use of fossil fuels. Linkola is also firm in rejecting human rights and individual freedoms as the cause of natural destruction. While prioritizing ecosystems over individual rights, this approach cannot be easily justified. Effective solutions to environmental challenges require a more holistic approach, including increased resource efficiency, adoption of green technologies, and changes in sustainable consumption behavior, thus maintaining ecological balance while respecting human rights.